EFEKTIVITAS ORGANISASI PEMERINTAH KECAMATAN MANGOLI TIMUR KABUPATEN KEPULAUAN SULA PROVINSI MALUKU UTARA - UMASANGAJI, KISBAR; DENGO, SALMIN; LONDA, VERY (Sam Ratulangi University, 2020)
The purpose of this rearch was to determine the organizational effectiveness of the East Mangoli DistrictGovernment. This research uses a qualitative descriptive approach. The organizational effectiveness of theEast Mangoli District government is seen from the five dimensions of organizational effectiveness, namelyproduction, efficiency, satisfaction, adaptation and development. The research informants were six people,namely the head of the sub-district, the head of the section, the staff / executor. Data collection usedinterview guidelines, while the analysis technique used was the interactive analysis model from Miles andHuberman. Based on the results of the data analysis, it was concluded that the effectiveness of thegovernment organization of the East Mangoli sub-district seen from the dimensions of production,efficiency, satisfaction, adaptation and development had not been maximized but was good enough. Basedon the research results, it can be recommended that: (1) To increase production, it is necessary to increasethe number of employees, increase the human resource capacity of employees through education andtraining; additional budget; and increasing the availability of work facilities and equipment. (2) Toincrease efficiency, it is necessary to utilize quickly and optimally the potential of employees' humanresources, budget / funds, and work facilities. (3) To increase employee satisfaction, it is necessary toincrease the fulfilment of intrinsic needs, especially employee welfare; (4) Increase responsiveness toevery external and internal development; and (5) To improve performance development, it is necessary toplan proper performance, increase the capacity and quality of human resources, and increase adequatework facilities, especially work technology equipment such as computers and their devices.Keywords: Effectiveness organization, government districts.